2019
DOI: 10.1177/1475921719834045
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional images generated from diffuse ultrasound wave: detections of multiple cracks in concrete structures

Abstract: The simultaneous detection of multiple defects in concrete structures is a task of pivotal importance for non-destructive testing and evaluation. Diffuse waves experiencing multiple scattering inside media are demonstrated to be sensitive to weak defects. Here, an analytic model is presented for diffuse wave decorrelation associated with sensitivity kernel that describes the time-of-flight distribution in strongly scattering environments. The model is then used for generating three-dimensional images that invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
(105 reference statements)
1
25
0
Order By: Relevance
“…More transducers and closer placement as well as analysis of different source-receiver pairs (i.e., sensor network) can lead to higher resolution. In a recent study, several other coda wave-based techniques such as maximum likelihood [ 23 ] and diffusion imaging [ 24 , 25 , 26 ] are developed for precise localization of cracks. Integrating them with this proposed technique will be an important task of our future work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More transducers and closer placement as well as analysis of different source-receiver pairs (i.e., sensor network) can lead to higher resolution. In a recent study, several other coda wave-based techniques such as maximum likelihood [ 23 ] and diffusion imaging [ 24 , 25 , 26 ] are developed for precise localization of cracks. Integrating them with this proposed technique will be an important task of our future work.…”
Section: Resultsmentioning
confidence: 99%
“…These features are well-known to severely affect the performance of traditional direct wave-based techniques. Fortunately, previous studies in the fields of optics, acoustic, and geophysics demonstrate that noise-like coda waves contain detailed information about internal structures, and they are very sensitive to changes occurring in the large volume of a medium [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. This sensitivity is attributed to the fact that coda waves propagate following complex trajectories not limited to the direct path between two sensors, and they may traverse the regions of interest repeatedly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These features are well-known to severely affect the performance of direct wave-based detection techniques. Fortunately, it has been demonstrated that coda wave is very sensitive to changes occurring in the large volume of a medium [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. This sensitivity is attributed to the fact that coda waves propagate following complex trajectories not limited to the direct path between sensors, and they may traverse the regions of interest repeatedly.…”
Section: Introductionmentioning
confidence: 99%